PROGNOSTIC VALUE OF MASKED UNCONTROLLED HYPERTENSION DEFINED BY DIFFERENT AMBULATORY BLOOD PRESSURE CRITERIA. (April 2021) - Coccina, Francesca; Pierdomenico, Anna Maria; Cuccurullo, Chiara; Vitulli, Piergiusto; Pizzicannella, Jacopo; Madonna, Rosalinda; Trubiani, Oriana; Cipollone, Francesco; Pierdomenico, Sante Donato
Abstract : Objective: Masked uncontrolled hypertension (MUCH), that is, normal clinic but high out-of-office blood pressure (BP) in treated hypertensive patients is at increased cardiovascular risk than controlled hypertension (CH), that is, normal clinic and out-of-office BP. Based on ambulatory BP, MUCH can be defined as daytime and/or nighttime and/or 24-hour BP above threshold values. It is unclear whether different definitions of MUCH show similar prognostic information. This study assessed the prognostic value of MUCH defined by different ambulatory BP criteria. Design and method: The occurrence of a composite end-point was evaluated in 738 treated hypertensive patients with normal clinic BP (<140/90 mmHg) who were selected from 2264 treated subjects. Participants were classified as having daytime MUCH (BP >135/85 mmHg) regardless of nighttime BP (Group 1), nighttime MUCH (BP >120/70 mmHg) regardless of daytime BP (Group 2), 24-hour MUCH (BP >130/80 mmHg) regardless of daytime or nighttime BP (Group 3), daytime MUCH only (Group 4), nighttime MUCH only (Group 5) and daytime + nighttime MUCH (Group 6). Results: There were 215, 357, 275, 42, 184 and 173 patients with MUCH from Group 1 to 6, respectively. During the follow-up (10 ± 5 years), 148 events occurred in patients with CH and MUCH. Results of univariate and multivariate Cox regression analyses are reported in the Table. Figure. No caption available. Conclusions: The prognostic impact of MUCH defined according to various ambulatory BP definitions may be different.